FACTORS RELATED TO THE SELECTION OF INJECTABLE CONTRACEPTION DEVICES IN THE PUS IN PALASARI CIATER VILLAGE, SUBANG REGENCY IN 2022 - Mustika, Mela; Karimah, Karimah; Soleha, Sri (HEARTY, 2025)
The maternal and Child Health program and family planning have a very important role in increasing the Human Development Index. One indicator of teh success of the MCH/KB program in the reduction in the maternal mortality rate (MMR) and the infant Mortality Rate (IMR). Couples of Reproductive age (PUS) are married couples whose reproductive organs are functioning properly between the ages of 20-45 years. Injectable family planning (KB) is a very effective contraceptive method for preventing pregnancy so that it is in great demand by couples of childceptives for couples of childbearing age (PUS) in the village of Palasari Ciater Subang. The method used was an analytical survey with a Cross Sectional Study design, the method of taking the sample using Stratified Random Sampling technique obtained a population of 65 people. The results of the study were described based on the education of the respondents, namely 48 people (73.8%) had high school education, based on parity with the multipara category, namely 54 people (78.5%) and based on the economy, most of them had an income of 1,000,000-2,000,000, namely 52 people (80%). From the results of the bivariate test, it can be seen that there is a relationship between education and the choice of injecting contraceptives because it obtains a value of p=0.049, there is a relationship between parity and the choice of contraceptives p=0.002, there is no relationship between the economy and the choice of injecting contraceptives because it obtains a value of p=0.483.